EFFECTS OF BIOCHAR AND CHROMOLAENA ODORATA LIQUID FERTILIZER ENRICHED WITH SODIUM BICARBONATE ON SOIL AND MUSKMELON (CUCUMIS MELO L.) - Jamilah, Jamilah; Yasman, Ari; Resigia, Elara; Ernita, Milda (Universitas Muhammadiyah Yogyakarta, 2020)
Biochar is an organic material instantly made by burning wood into charcoal by pyrolysis, which can meet the high demand for an organic material that cannot be available in a short time. The study aimed to determine the effect of biochar and Chromolaena odorata liquid fertilizer (CLF) enriched with Sodium bicarbonate on soil pH and Muskmelon (Cucumis melo L.) productivity. The research was conducted from December to February 2019 at the field station of Tamansiswa University, Padang. The study was carried out in a factorial experiment with 2 treatment factors arranged in a Completely Randomized Design, consisting of three replications within treatments. The data obtained were analyzed using the F test at 5%, followed by the Least Significant Difference (LSD) test at 5%. The results showed that there was an interaction effect of Biochar and CLF application on reducing the soil pH. Among all treatments, the application of 2 t.Ha-1 biochar combined with 50 ml.L-1 CLF + 0 g.L-1 sodium bicarbonate resulted in the highest growth rate and yield of muskmelon in Ultisols soil.